Credit conditions and tenure choice: A cross-country examination - David Cronin; Kieran McQuinn (The Economic and Social Research Institute (ESRI), 2017)
An understanding of the house price to rent ratio and its determinants is important in assessing housing market developments and tenure choice therein. While the ratio is most usually explained by the user cost of capital, the influence of credit conditions on it has been added to econometric assessments in recent years. Using a new cross-country panel, we estimate the impact of variations in credit conditions on the house price to rent ratio between 1994 and 2015 on both a panel and country-by-country basis. This period was one of substantial cross-country house price movements as developments in standard explanatory variables, such as income levels, interest rates and demographics, were accompanied by major changes in credit markets. In line with other recent studies, our results establish the relevance of credit conditions to the house price to rent ratio at both panel and country levels. Moreover, the evidence points to credit conditions dominating the user cost of capital over the sample period, emphasising the need to include credit analysis when evaluating housing market developments.
Keywords: G12; R21; R30; 330; House Prices; Rents; Credit